Surveillance of H. pylori prevalence and antibiotic resistance in the urban Chinese population: a nationwide multi-center study - Dr Liang Wang (International Journal of Infectious Diseases)
Introduction: China has a high antibiotic-resistant H. pylori infection burden. The current knowledge of H. pylori prevalence and antibiotic resistance in China is mainly based on meta-analysis and systematic review. In addition, since H. pylori prevalence is tightly associated with economic development, the H. pylori infection and antibiotic resistance rates in the urban Chinese population may be significantly changed due to the rapid socioeconomic development over the past twenty-year urbanization. However, the actual situation is unknown. Therefore, this study conducted a nationwide, multi-center, cross-sectional surveillance using the string test coupled with qPCR to provide an accurate overview of H. pylori prevalence and antibiotic resistance to clarithromycin and levofloxacin in urban China. Methods: From March to November 2023, 12,902 individuals aged from 18 to 60 years old were recruited from 52 cities belonging to 26 out of 31 provinces in mainland China. All the individuals were examined for H. pylori infection and antibiotic resistance to clarithromycin and levofloxacin via quantitative PCR of gastric fluid samples collected through string test. All results were statistically analyzed via univariate analysis. Results: Among all participants, the average individual-based H. pylori infection rate in urban China was 27.08%. Among 26 out of 31 provinces, the infection rates of H. pylori ranged from 15.25% in Hunan to 41.47% in Fujian. According to the division of seven geographic regions, Eastern China has the highest H. pylori infection rate of 32.45%. As for antibiotic resistance of H. pylori, the average clarithromycin resistance rate is 50.82%, while the average levofloxacin resistance rate is 47.17%. Discussion: The investigation discloses that the prevalence of H. pylori among urban Chinese is notably lower than previous reports. This variance, indicative of improvement, can be attributed to the progressive enhancement of sanitary conditions and advancements in medical care within urban regions of mainland China over the preceding two decades. In addition, it was found that the resistance rates to clarithromycin and levofloxacin are unexpectedly high in the urban Chinese population. This may be related to the increased use of antibiotics to treat gram-negative bacterial infections. It is imperative to highlight the strengths of this investigation, which encompass the application of a singular methodology for precise evaluation of the present prevalence of H. pylori and antibiotic resistance within the urban Chinese population. Meanwhile, notable limitations of this study involve discrepancies in sample sizes and the absence of data from five provinces. Conclusion: This study updates our understanding of the current prevalence and antibiotic resistance to clarithromycin and levofloxacin of H. pylori in urban China. This suggests that future public health strategies should focus on managing antibiotic use, and susceptibility-guided therapy should be adopted for clinical practice to help improve the successful eradication of H. pylori infection.